Desmoglein-2 mutations in propeptide cleavage-site causes arrhythmogenic right ventricular cardiomyopathy/dysplasia by impairing extracellular 1-dependent desmosomal interactions upon cellular stress. Issue 2 (17th December 2019) - Vite, Alexia; Gandjbakhch, Estelle; Hery, Tiphaine; Fressart, Veronique; Gary, Francoise; Simon, Francoise; Varnous, Shaida; Hidden Lucet, Francoise; Charron, Philippe; Villard, Eric
Abstract: Aims: Desmoglein-2 ( DSG2) mutations, which encode a heart-specific cadherin crucial for desmosomal adhesion, are frequent in arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D). DSG2 mutations have been associated with higher risk of biventricular involvement. Among DSG2 mutations, mutations of the inhibitory propeptide consensus cleavage-site (Arg-X-Arg/Lys-Arg), are particularly frequent. In the present work, we explored the functional consequences of DSG2 propeptide cleavage site mutations p.Arg49His, p.Arg46Trp, and p.Arg46Gln on localization, adhesive properties, and desmosome incorporation of DSG2. Methods and results: We studied the expression of mutant-DSG2 in human heart and in epithelial and cardiac cellular models expressing wild-type or mutant (p.Arg49His, p.Arg46Trp, and p.Arg46Gln) proDSG2-GFP fusion proteins. The consequences of the p.Arg46Trp mutation on DSG2 adhesiveness were studied by surface plasmon resonance. Incorporation of mutant p.Arg46Trp DSG2 into desmosomes was studied under low-calcium culture conditions and cyclic mechanical stress. We demonstrated in human heart and cellular models that all three mutations prevented N-terminal propeptide cleavage, but did not modify intercellular junction targeting. Surface plasmon resonance experiments showed a propeptide-dependent loss of interaction between the cadherin N-terminal extracellular 1 (EC1) domains. Additionally, proDSG2 mutant proteins were abnormally incorporated into desmosomes under low-calcium culture conditions or following mechanical stress. This was accompanied by an epidermal growth factor receptor-dependent internalization of proDSG2, suggesting increased turnover of unprocessed proDSG2. Conclusion: Our results strongly suggest weakened desmosomal adhesiveness due to abnormal incorporation of uncleaved mutant proDSG2 in cellular stress conditions. These results provide new insights into desmosomal cadherin regulation and ARVC/D pathophysiology, in particular, the potential role of mechanical stress on desmosomal dysfunction.